The Status of the Audience in New Advertising Policies (With a Focus on Iran) - Hosseini, Seyed Mehdi; Emamifar, Seyed Nezamoddin (Business, Marketing, and Finance Open, 2025)
The aim of this study is to investigate the new status of the audience in contemporary advertising policies, with a particular focus on Iran. This research seeks to demonstrate how media, interactive technologies, and new message design strategies have redefined the relationship between advertising and its audience. Today’s audience is not merely a passive recipient of messages but plays an active role in meaning-making and influencing the effectiveness of advertisements. The research employs a qualitative and fundamental methodology, utilizing library research, document analysis, and content analysis of 250 domestic and international advertising samples from 2010 to 2020. Advertisements were analyzed based on interactive elements, design types, persuasion strategies, and audience responses. Data collection tools included print and electronic sources, images, and analytical forms. Findings indicate that new technologies—such as interactive media, advanced graphics, augmented reality, and experience-oriented design—have transformed the position of the audience. The audience has shifted from a passive role to that of a meaningful agent. Examples such as the Delester interactive billboard or Apple Vision Pro augmented reality glasses illustrate the active role of the audience in engagement, psychological persuasion, and advertising experience. The study concludes that the success of advertising depends on recognizing the audience as an active element. Effective advertisements are those that allow the audience to participate, experience, and choose, making the message memorable by stimulating cognitive, emotional, and sensory responses.